Sleep Quality in Patients Presenting with Rheumatoid Arthritis at Tertiary Care Hospital, Islamabad - Avinash Punshi, Soman Prithiani, Mohan Lal Kirpal Das Talreja, Komal Bai, Uzma Rasheed, Avinash Bhaktiarpuri (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the sleep quality in patients presenting with rheumatoid arthritis. Study design: Cross-sectional study. Place and duration of study: Department of Rheumatology, PIMS, Islamabad from 1st September 2022 to 28th February 2023. Methodology: One hundred and forty-three patients with rheumatoid arthritis (RA) were enrolled. The age of the patients was between 40-80 years. The sleep quality was assessed in both groups and compared to assess the effect of rheumatoid arthritis on sleep quality. The patients were divided into two groups. Group A was those having non-optimal sleep duration. In contrast, group B was those who had optimal sleep duration. The sleep quality assessing tool Pittsburg Sleep Quality Index was applied to assess the disease activity and the patient’s sleep quality. Disease activity was assessed using Visual Analogue Scale (VAS), Clinical Disease Activity Index (CDAI), and Health Assessment Questionnaire Disability Index (HAQ-DI). Result: The mean age of the patients was 51.2±9.61 years, with patients having a non-optimal sleep slightly younger than optimal. Most of the cases were females. Non-optimal sleep group has slightly higher disease activity than the optimal sleep group. The optimal sleep was observed in only 44.2% of cases, while non-optimal sleep was observed in 55.8%. Higher sleep disturbance was observed in patients with high VAS and increased snoring and awakening short of breath with headaches. Practical implication: The significance of this study is providing factors associated with poor sleep quality in rheumatoid arthritis patients and thus assisting in generating management protocols of such cases for better health outcomes and sleep quality. Conclusion: Rheumatoid arthritis patients have an increased prevalence of non-optimal sleep strongly associated with increased pain levels. Keywords: Sleep quality, Rheumatoid arthritis, Tertiary care hospital